EFEKTIVITAS MIKROORGANISME ANTAGONIS TERHADAP PENYAKIT KARAT PUTIH PADA TANAMAN KRISAN (Chrysanthemum morifolium Ramat) DI KOTA TOMOHON - Aprilia N. Rares; Emmy Senewe; Guntur S.J. Manengkey; Max M. Ratulangi (Universitas Sam Ratulangi, 2015)
ABSTRACT Chrysanthemum or Chrysanthemum marifolium Ramat is one of the types of cut flowers have bright market prospects. As one of the types of ornamental plants, dubbed